Tackling Wicked Government Problems - JACKSON NICKERSON,, RONALD SANDERS (Brookings Institution Press, 2013)
This growing crisis in enterprise leadership and what to do about it is the focus of this book. Just over a year ago, the Brookings Institution, through Brookings Executive Education and Olin Business School, and with the support of Booz Allen Hamilton, sponsored a symposium on the leadership challenges of wicked government problems. A small but eclectic group of leadership practitioners and scholars who had been thinking about that challenge came together in that symposium to examine the crisis. Their thoughts, now in the form of the chapters that follow, serve as a forum for how to address the current challenges of leading the federal enterprise. It is our hope, as well as the hope of the contributors to this book, that the forum stirs much discussion, debate, and, ultimately, progress. In that regard, we would like to express our appreciation to our contributors, many of whom are â€œsittingâ€ federal officials, for their compelling insights into the emerging theory and practice of enterprise leadership. We would also like to thank our respective employersâ€” Olin Business School at Washington University in St. Louis for Dr. Nickerson and Booz Allen Hamilton for Dr. Sandersâ€” for giving us the time and support to launch this discussion; without their generosity the book would not have been possible. It also would not have been possible without the tireless efforts of Dr. Rachel Mendelowitz, a Booz Allen Hamilton colleague, who along with Carolyn Mauriello, also of Booz Allen Hamilton, gave much of their own time to keep us all on track, in terms of both substance and process.